Sediment Enrichment Ratio and Nutrient Leached by Runoff and Soil Erosion on Cacao Plantation - Oteng Haridjaja (UNIVERSITY OF LAMPUNG, 2012)
Soil consevation management system is an activity for diminishing sediment enrichment ratio and nutrient leacheds by water run off and soil erosion processes. The research was aimed to study sediment enrichment ratio and nutrient leached by run off and soil erosion on cacao plantations. Arachis pintoi with strips parallel contour and multiple strip cropping of upland rice or soybean (Glycine max) were planted to improve soil physical characterictic on cacao plantation as a main plant. The expriment were conducted with treatments as 10-15% and 40-45% slopes, 5-7 months and 25-27 months cacao ages (as main plants). As sub plots are T1 as a monoculture which to be cleaning under the plant canopy, T2 as a multiple strip cropping of upland rice or soybean, T3 as a combination of T2 and A. Pintoi strip. The results showed that total N, P2O5, and K2O and organic-C contents in water run off and soil sediments indicated that T3 >T2 >T1 treatment, with the contents of each nutrient: T3 (total N 0.18%; 24.87 mg 100 g-1 P2O5: K2O 15.16 mg 100 g-1), T1 (total N 0.16%, 22.39 mg 100g-1 P2O5, K2O 11.50 mg 100g-1). The total N, P2O5, K2O and organic-C soil contents < accumulation nutrient contents of total water run off and soil sediment transport. All of treathments have sediment enrichment ratios > 1.